2006
DOI: 10.1021/jo060160e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-Phosphonopyrroles via a One-Pot RCM/Oxidation Sequence

Abstract: A four-step synthesis of 2-phosphonopyrroles is presented starting from suitable aldehydes. The key step in the synthesis involves a one-pot ring-closing metathesis/oxidation sequence of a functionalized alpha-aminoalkenyl phosphonate. Notwithstanding the presence of a nucleophilic nitrogen atom and high substitution patterns in the substrate, the results of the RCM reaction are excellent using mild reaction conditions. Furthermore, a synergism is observed between the RCM catalyst and the oxidizing agent, caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Finally, evaluating 44 23b as a substrate showed that no metathesis occurred at all when a 2‐methylallyl substituent is introduced at nitrogen (Scheme 10). Initiation at either double bond would result in a ruthenium species 45 or 46 with limited steric hindrance at the other double bound, especially compared to intermediates 19 in Scheme 4.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, evaluating 44 23b as a substrate showed that no metathesis occurred at all when a 2‐methylallyl substituent is introduced at nitrogen (Scheme 10). Initiation at either double bond would result in a ruthenium species 45 or 46 with limited steric hindrance at the other double bound, especially compared to intermediates 19 in Scheme 4.…”
Section: Resultsmentioning
confidence: 99%
“…Following the general procedure, 2j was obtained from 1j (2.46 g, 20 mmol) as a colorless liquid (3.49 g, 86%). 1 H NMR (300 MHz, CDCl 3 ) δ 6.78 (d, 2H, J = 9.2), 6.66 (d, 2H, J = 9.2), 5.82 (ddt, 2H, J = 17.2, 10.3, 5.0), 5.16 (dddd, 2H, J = 17.2, 1.6, 1.3, 1.3), 5.12 (dddd, 2H, J = 10.3, 1.6, 1.2, 1.2), 3.82 (dt, 4H, J = 5.0, 1.5), 3.68 (s, 3H); 13 (46), 134 (49), 120 (34), 92 (24), 77 (32), 41 (100), 39 (56). (22), 188 (26), 146 (26), 130 (18).…”
Section: N-(3-(diallylamino)phenyl)acetamide (2h)mentioning
confidence: 99%
“…32 Shortly afterwards, the same authors reported a one-flask RCM-aromatization sequence, using chloranil as a stoichiometric oxidant. 33,34 For the synthesis of N-aryl pyrroles, a subsequent dehydrogenation catalyzed by Pd/C has been described for one example, 35 and it has been reported that conducting the RCM under microwave conditions results in remarkably high yields of pyrroles in most cases. 36,37 In the furan series, one-flask sequences consisting of diallyl ether RCM and stoichiometric oxidation using NiO 2 38 or benzoquinones 39,40 have been described.…”
Section: Introductionmentioning
confidence: 99%
“…A tandem RCM/oxidation strategy proved productive in the straightforward one-pot synthesis of valuable carbocyclic and heterocyclic compounds based on orthogonal catalysis with Grubbs' second generation catalyst (4) associated with a dehydrogenation agent [44][45][46]. Thus, diallylamines (e.g.…”
Section: Tandem Rcm/oxidationmentioning
confidence: 99%
“…The general applicability of these tandem reactions was demonstrated on a number of substrates producing a variety of pyrroles in good to excellent yields. Taking [45].…”
Section: Tandem Rcm/oxidationmentioning
confidence: 99%